Campur Kode pada Novel Tentang Kamu Karya Tere Liye - Ida Ayu Made Anggi Pradewi; Ni Wayan Arnati; I Made Madia (Stilistika : Journal of Indonesian Language and Literature, 2022)
This research is entitled "Mix Code in Tere Liye's Novel About You". The problems that will be discussed in this study are the types of code mixing, the origin (source) of code mixing, and the factors causing code mixing. The purpose of this study is to explain the types and factors of code mixing contained in Tere Liye's novel About You. The method used in this research is the referential method. This research uses sociolinguistic theory and bilingual theory. The results of this study reveal that in the novel About You, there are various types of code mixing, namely, the first type of code mixing based on mixed language, namely internal code mixing, external code mixing. The types of code mixing based on the linguistic level are divided into two types, namely the word level and the phrase level. Code mixing at the word level is divided into basic words, affixed words, compound words, and pronouns. Second, the origin (source) of inward code mixing comes from regional languages, and outward code mixing comes from foreign languages. Third, the factors causing code mixing are influenced by speaker factors; seen from the background of speakers, and language factors; seen from the limitations of the choice of words that are shorter, popular, and prestigious.